Studies of polyoma virus DNA: cleavage map of the polyoma virus genome. - Chen, M C (1975)
A small-plaque polyoma virus, MPC-1, was isolated from a mouse plasmacytoma. The DNA of this polyoma virus was cleaved with a restriction enzyme from Haemophilus influenzae (Hin d), and the molecular weights of the limit products were analyzed by electrophoresis and electron microscopy. The fragments produced by this enzyme have been ordered by analysis of partial digest products. A physical map of the polyoma virus genome was then constructed.